Atrial myopathy: a pathogenic mechanism linking atrial fibrillation and ischemic stroke - Kahadi, Cik; Rizal, Ardian (Heart Science Journal, 2025)
Atrial myopathy (AM) has become a topic of study for many years. Atrial Myopathy is characterized as "any variety of architectural, structural, electrophysiological, or contractile abnormalities altering the atria, which can result in clinically significant manifestations," and is associated with atrial dysfunction and dilatation. Evidence shows that atrial myopathy (AM) contributes to atrial fibrillation and embolic strokes of unknown origin. Atrial myopathy or disease provides a substrate leading to atrial fibrillation (AF) and contributes to a chance of atrial thrombus development and, finally, stroke. However, following clinical trials have opposed this point of view. Additionally, ischemic strokes are categorized as cryptogenic when an embolic stroke occurs without a known related etiology (embolic stroke of undetermined source, ESUS). This led to the concept of atrial myopathy, showing that a dysfunctional atrium may result in stroke without the incidence of atrial fibrillation. Atrial interstitial fibrosis, extracellular matrix deposition, and inflammation may trigger and perpetuate atrial myopathy, resulting in blood stasis inside the atria and potentially resulting in stroke without any intervening atrial fibrillation. This paper describes an overview of Atrial Myopathy in pathogenic mechanisms linking atrial fibrillation and ischemic stroke. Atrial myopathy is not only a substrate for atrial fibrillation and makes thrombus formation cause ischemic stroke, but also leads to blood stasis within the atria and makes ischemic stroke without intervening atrial fibrillation.